THE IMPACT OF SERVICE QUALITY ON HOSPITAL IMAGE: THE MEDIATING ROLES OF PATIENT SATISFACTION AND TRUST - Stella Abigail; Rahayu Puji Suci; Irfany Rupiwardani; Aji Suraji; Asih Tri Rachmi Niswantari (Yayasan Adra Karima Hubbi, 2026)
The way a hospital looks plays a positive part in forming patients’ views and affecting their choices to seek medical care. This study seeks to investigate the impact of service quality on hospital image, as mediated by patient satisfaction and trust. This study’s population consisted of 351 outpatients from Rumah Sakit Permata Bekasi. Questionnaires were used to data collect, which was then analyzed using SEM-PLS software’s Partial Least Squares (PLS) approach. The results indicate that service quality has a substantial effect on patient satisfaction, service quality substantial affects patient trust, good service quality substantial impacts the hospital image, patient satisfaction does not substantial influence hospital image, patient trust substantial affects hospital image, patient satisfaction does not mediate the relationship between service quality and hospital image, and patient trust substantial mediates the Based on these findings, the study suggests that hospitals should boost broader factors such as communication management and hospital image management on social media, which can improve public opinion of the hospital while also optimizing service quality and overall hospital image.